The Oxford book of modern science writing - Dawkins, Richard, 1941- (Oxford ; New York : Oxford University Press, 2008)
The Oxford Book of Modern Science Writing is a celebration of the finest writing by scientists for a wider audience - revealing that many of the best scientists have displayed as much imagination and skill with the pen as they have in the laboratory. This is a rich and vibrant collection that captures the poetry and excitement of communicating scientific understanding and scientific effort from 1900 to the present day. Professor Dawkins has included writing from a diverse range of scientists, some of whom need no introduction, and some of whose works have become modern classics, while others may be less familiar - but all convey the passion of great scientists writing about their science.
Part I: What Scientists Study -- Part II: Who Scientists Are -- Part III: What Scientists Think -- Part IV: What Scientists Delight In.
Includes bibliographical references and index.
1
Keywords: Science; Scientists$1 (Bwritings.s